Assessment of extended urine protein monitoring frequency in patients receiving bevacizumab. (June 2021) - Schiffer, Molly; Zukovic, Lejla; Hall, Sophia; Merl, Man Yee
Purpose: Proteinuria monitoring is required for patients receiving bevacizumab. Nonetheless, the frequency of monitoring is not specified in the package insert. A 2014 quality improvement study performed at Yale New Haven Health System (YNHHS) found that proteinuria occurred in 15% (all grade) of the 162 patients evaluated. These results led to decreasing the frequency of proteinuria monitoring from every treatment to every other treatment. The objective of this study is to assess the safety of the extended interval for urine protein (UP) monitoring. Methods: Patients receiving at least four bevacizumab treatments at YNHHS from January to June 2017 were randomly selected and retrospectively reviewed. The following data were collected: baseline patient characteristics, comorbidities, medication history, and proteinuria monitoring. The grade, prevalence and management of proteinuria were evaluated. The minimum necessary sample size was determined to be 384 treatments to achieve a 95% confidence interval. Results: Fifty-five patients and 388 bevacizumab treatments were evaluated. Urine protein was assessed in 52.5% of treatments. The incidence of proteinuria among patients was 7.2% (grade 2) and 0% (grade 3). Cumulative dose and the number of total bevacizumab doses did not affect the timing for onset or severity of proteinuria. Two patients with UP ≥ 2+ were further monitored using a 24-h urine collection test with negative results. No treatments were held due to proteinuria. Conclusion: Monitoring proteinuria every other treatment does not increase the frequency of adverse events. Urine protein is now monitored prior to every third bevacizumab treatment, reducing unnecessary labs and chair time.